Studies on immunostimulants and innate immune gene expression in Atlantic salmon: candidate tools for marker selection - Mostazo, Miriam Guadalupe Contreras, 1991- (2015)
The aim of this project was to create tools to select robust fish with better innate immunity for breeding stock. The project was divided into three main stages. The first stage was to study basal expression of antimicrobial peptides (AMP) and inducible nitric oxide synthase (iNOS) of different Atlantic salmon (Salmo salar) families and investigate the effect of calcium supplemented β-Hydroxy-β-methyl butyrate (calcium-HMB) and β-Hydroxy-β-methyl butyrate (HMB) in the diet and water, as inductors of expression of these genes. The second stage was to test if increased expression of these genes has a defense role against bacterial and virus infection and the third stage was to initiate a search for single nucleotide polymorphism (SNP) markers in order to use them as selection markers for fish high-tolerance against pathogen infections. For the first stage, two different experiments were performed. In the first experiment, gill lamella tissue of 1330 fish (133 families and 10 fish per family) were collected in order to study basal expression of Cathelicidin-2 (CATH-2), an important component for the first line of immune defenses. In addition, 14 families were selected, treated with calcium-HMB and, then, gill tissues were collected and analyze in order to study the induction of CATH-2. Different basal expression of CATH-2 was observed and we could see induction of expression in two of the 14 families. Calcium-HMB treatment did not work as expected, possibly due to the presence of calcium; therefore, we decided to change the treatment. In the second experiment, gill and skin tissues of 12 families (12 individuals per family) of Atlantic salmon were collected in order to investigate induction of CATH-2, Hepcidin-1 (Hep-1) and inducible nitric oxide synthase (iNOS), by adding HMB in the diet and water. Up-regulation of CATH-2 in gill samples and CATH-2 and iNOS in skin samples was observed in all the families. Interestingly, Hep-1 expression in skin samples, rather than being enhanced, was in some cases ...